Business cycles in oil exporting countries: A declining role for oil? - Salman Huseynov; Vugar Ahmadov (Graduate Institute of International and Development Studies, 2014)
In this study, we investigate the nature and possible sources of economic fluctuations in oil exporting countries using principle component and impulse-response analysis. The principal component analysis shows that the first two components can be statistically significantly explained by world GDP, but not by oil prices. We further develop our study using impulse-response analysis and find that a global demand shock is as important as oil supply and oil demand shocks in determining the dynamics of macroeconomic variables of interest. Though previous studies in this field underline the importance of institutional factors, we find that rising global political and economic integration can play a critical role in explaining business cycles of these economies. With increasing integration into the world economic system, oil exporting countries have become more susceptible to world business cycles, the sources of economic fluctuations have become more diversified, and consequently, the role of oil has declined over time. These results have crucial policy implications for the role of the fiscal and monetary policy in managing economic fluctuations in these economies.
Keywords: C11; C32; E30; E32; 330; cycles; oil exporting countries; oil price; Bayesian methods